FAKTOR DETERMINAN INDEKS PEMBANGUNAN MANUSIA DI INDONESIA - Marihot Nasution (Pusat Kajian Anggaran, 2019)
The human development index (HDI) is one indicator of development progress in aspects of human quality in a country. This study aims to identify the factors that affect the human development index in Indonesia by taking a sample of 34 provinces in Indonesia during the period 2013 to 2017. The analysis technique used is panel data regression using the fixed effect model. The regression results show that the gross regional domestic product (PDRB) per capita and the provincial poverty level have an influence on the high and low human development index. While the variable unemployment rate and fiscal independence ratio do not have a significant effect on HDI. These results imply the importance of regional economic development and poverty alleviation for the sake of increasing the human development index.